The role of internal droplet size on emulsion stability and the extraction performance of kraft lignin removal from pulping wastewater in emulsion liquid membrane process - Ooi, Zing Yi (Taylor and Francis Inc., 2016)
It has been discovered that the size of internal droplets in primary emulsion determines emulsion dispersion and stability in emulsion liquid membrane (ELM) process for removal of lignin from pulping wastewater. Generally, primary emulsion contains kerosene, Aliquat 336, sodium bicarbonate, as well as Span 80 as diluent, carrier, internal phase, and surfactant, respectively. Hence, this study had looked into the parameters, including concentration of surfactant, carrier, and stripping agent; emulsification speed and time; as well as agitation speed and time. As a result, the diameter of the smallest droplets (1.4 µm) was formed with maximum lignin extraction (95%), minimum swelling (5%) at 3% (w/v) surfactant concentration, 12,000 rpm of emulsification within 5 minutes, 0.01 M of Aliquat 336, 0.1 M of NaHCO3, and 250 rpm of extraction within 10 minutes.